Comparative study of rice and Arabidopsis actin-depolymerizing factors gene families - Feng, Ying (Journal of plant physiology, 2006)
Actin-depolymerizing factors (ADF) is one of the small actin-binding proteins that regulate actin dynamics in cells. Analysis of the complete rice and Arabidopsis protein sequences revealed 12 ADF proteins, respectively. A further study on the similarities and differences between ADF throughout rice and Arabidopsis genome was carried out at the level of genomic organization and protein structure. The strict conservation of essential structural features suggested that the mode of action and physiological function of these proteins, as well as the expression pattern of their coding genes, might be very similar. The ADF proteins were divided into four groups based on the phylogenetic relationships of the amino acid sequences, and was comparable with previous studies